2011
DOI: 10.1074/jbc.m111.300889
|View full text |Cite
|
Sign up to set email alerts
|

Tagetitoxin Inhibits RNA Polymerase through Trapping of the Trigger Loop

Abstract: Background: Antibiotic tagetitoxin inhibits bacterial RNA polymerases (RNAPs) and RNAP III from eukaryotes. Results:We constructed a structural model of tagetitoxin bound to the transcription elongation complex. Conclusion: Tagetitoxin interacts directly with the ␤Ј subunit trigger loop, stabilizing it in an inactive conformation. Significance: Results have implications for designing new antibiotics and understanding principles of RNAP functioning and regulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(68 citation statements)
references
References 33 publications
5
60
3
Order By: Relevance
“…The structure of bacterial RNA polymerase with the inhibitor Tagetitoxin (Tgt) indicated that Tgt stabilizes an inactive state by changing metal ion binding in the active site [91,93]. However, a recent EC-Tgt model based on biochemical analysis and molecular dynamic simulations suggested that Tgt inhibits transcription by trapping the trigger loop in an inactive state [94]. Thus the mechanism of Tgt inhibition remains debated [95,96].…”
Section: Translocation and Inhibitionmentioning
confidence: 99%
“…The structure of bacterial RNA polymerase with the inhibitor Tagetitoxin (Tgt) indicated that Tgt stabilizes an inactive state by changing metal ion binding in the active site [91,93]. However, a recent EC-Tgt model based on biochemical analysis and molecular dynamic simulations suggested that Tgt inhibits transcription by trapping the trigger loop in an inactive state [94]. Thus the mechanism of Tgt inhibition remains debated [95,96].…”
Section: Translocation and Inhibitionmentioning
confidence: 99%
“…Interestingly, small molecules may further modify the mobile active centres. The antibiotic tagetitoxin binds in the vicinity of the catalytic residues of the TL (Artsimovitch et al, 2011;Vassylyev et al, 2005). Whilst not affecting the catalytic properties of the TL active centre (Yuzenkova et al, 2013), tagetitoxin modifies it so that, after phosphodiester bond formation, RNAP with the 'TL+tagetitoxin' active centre has a delayed translocation (Yuzenkova et al, 2013).…”
Section: Multiple Active Centres Of Rnapmentioning
confidence: 99%
“…We identified a plausible Tgt-binding site 16 near the previously reported binding site in the T. thermophilus RNAP holoenzyme. 2 Binding of Tgt to this site is sterically incompatible with the fully-folded TL but is compatible with an alternative, "inactive" state stabilized by a contact between Tgt and the TL residue β' Arg1239 (Arg933 in the E. coli β' subunit).…”
Section: Tgt Contacts With the Tlmentioning
confidence: 92%